THE INFLUENCE OF NUTRITION AND LIFESTYLES ON BONE HEALTH IN PATIENTS WITH SCHIZOPHRENIA AND DEPRESSION - Bajic, Biljana; Ristić, Svetlana; Palibrk, Marija; Arnaut, Aleksandra; Curcic, Svetlana; Tausanovic, Katarina (Medicinski časopis, 2020)
Objective. The aim of this paper is to investigate the influence of nutrition and pattern behaviors on bone health in people with mental health disorders.Methods. A cross-sectional study has been conducted at the Clinic for Psychiatry of the Clinical Center of Kragujevac and at the Department of Neuropsychiatry of the Specialist-Consultative Service of Health Care CenterKragujevac .The survey included 46 patients from the age of 22 to 81, both genders, with schizophrenia as a diagnosis for mental disorders and depression determined by a psychiatrist. Quantitative testing of calcium, magnesium, phosphorus, sodium and potassium has been performed by standard biochemical methods. Vitamin D has been determined by HPLC method (high performance/pressure liquid chromatography) i.e. by a liquid chromatography under high pressure.Results. In the whole group of patients tested, 58.7% of patients were physically active and the patients with schizophrenia (p = 0.026) were less physically active. Out of the total number, 67% of patients eat irregularly and this habit is more present in patients with schizophrenia (p = 0.003). In terms of the presence of certain nutrients, fish is more represented in the nutrition of people suffering from depression. Three patients (6.5%) reported osteoporosis in their medical history, one of whom had a spontaneous fracture. In the anamneses (6.5%) of the patients stated that their parents had had spontaneous bone fractures. Low values of 25 (OH) D in the serum were present in both study groups.Conclusion. Unhealthy lifestyles, low level of Vitamin D found in people who have mental health disorders represent risk factors for the reduced bone mass. The results of our research indicate the need for timely identification of potential risk factors and improvement of prevention in order to raise awareness of the importance of healthy lifestyles and behavior modification.
Keywords: mental disorders; risk factors; lifestyle; bone diseases, metabolic; vitamin D.